Analisis Faktor yang Mempengaruhi Pemilihan Obat Generik atau Bermerek pada Mahasiswa Analis Kesehatan Universitas Indonesia Timur - Asnurbaety Dwiyana (Jurnal Media Laboran, 2017)
Drugs are materials or alloys, including biological products used to influence or investigate physiological or pathological systems for diagnosis, prevention, healing, recovery, health promotion and contraception for humans. In the treatment of a disease is not always used drugs, often massaged, scraped with coins, surgery, cut, and so on, but most use drugs. The purpose of this study is to determine the main factors that affect the selection of generic drugs or branded drugs on Health Analyst Students of the University of East Indonesia. The type of this research is analytical survey research using cross sectional study approach that is the measurement conducted only once. Subjects studied were Health Analyst Students with a large sample of 162 people. The sampling method used is simple random sampling. The results showed that there was influence between the security and the price of the drug with the p value of 0.034 and 0,000 respectively on the type of selection of generic drugs or branded drugs on the students, while the knowledge, efficacy and quality of drug p value of 0.054 respectively; 0.201; 0.985 indicates no effect. Based on the results of research, the main influence on the selection of generic drugs or branded drugs in students is the price of drugs with a value of 0.000 p